1981
DOI: 10.1677/joe.0.0910043
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Metabolism of [3h]testosterone in Vitro by the Epididymis of the Immature Rat

Abstract: We examined the production in vitro of 5 alpha-reduced metabolites from testosterone by the rat epididymis during pubertal maturation. Minced caput and cauda epididymides from 30-,45-, and 55-day-old rats were incubated with [3H] testosterone for 2h. Analysis of the radioactive metabolites revealed both similarities and differences in the metabolic patterns compared to those reported for adult rats. As in adults, 5 alpha-dihydrotestosterone was the most abundant metabolite produced by both epididymal segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…DISCUSSION A previous study of in-vitro [3H]testosterone metabolism by the immature rat epididymis indicated that the same metabolites are formed as in adult tissue but in different proportions (Foldesy & Leathem, 1981a). The present results suggest that the effects of androgen withdrawal upon androgen metabolism by the immature rat epididymis may differ also from those observed in adults.…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…DISCUSSION A previous study of in-vitro [3H]testosterone metabolism by the immature rat epididymis indicated that the same metabolites are formed as in adult tissue but in different proportions (Foldesy & Leathem, 1981a). The present results suggest that the effects of androgen withdrawal upon androgen metabolism by the immature rat epididymis may differ also from those observed in adults.…”
Section: Resultssupporting
confidence: 50%
“…Tissue incubations and analysis of radioactive metabolites The incubation procedure, and the analysis and identification of radioactive metabolites are presented in a companion study (Foldesy & Leathem, 1981a). Briefly, excised epididymides were severed at the mid-corpus region to give caput and cauda segments which were then minced and incubated separately in 5 ml Krebs-Henseleit bicarbonate buffer with 5ng…”
Section: Animal Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In older men, a decrease in zinc removal from the tail outer dense fiber during epididymal maturation was correlated with a decrease in motility. Furthermore, reports have indicated an age-related decrease in biochemical parameters including testosterone, fructose and accessory gland functions resulting in the decline in sperm motility with age [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%